Grade 10 Functions and Graphs Answers
Grade 10 Functions and Graphs Answers
Grade 10 Functions and Graphs Answers
3. a) 𝑦 = 3 − 2𝑥 b) 𝑦 = 𝑥2
c) 𝑦 = 2𝑥
d) We have coordinates (-3; 5) and (0; 3) This is the y-intercept or c value.
This means 𝑦 = 𝑚𝑥 + 3 Now we substitute in the other coordinate
5 = 𝑚(−3) + 3
2 = −3𝑚
2
∴ 𝑚 = −3
2
Our equation is ∴ 𝑦 = − 𝑥 + 3
3
2|Page
4. a)
b)
3|Page
c)
d)
4|Page
Activity 2
1. a)
b)
5|Page
c)
d)
6|Page
2. a) The points from the graph can be seen as (0; 4) and (-3; 0).
So, we have 𝑦 = 𝑚𝑥 + 𝑐 and substituting in (0; 4) gives
4 = 𝑚(0) + 𝑐
∴𝑐=4
𝑦 = 𝑚𝑥 + 4
4
Our equation of the line is ∴ 𝑦 = 3 𝑥 + 4
b) The points from the graph can be seen as (0; 2) and (5; 0).
So, we have 𝑦 = 𝑚𝑥 + 𝑐 and substituting in (0; 2) gives
2 = 𝑚(0) + 𝑐
∴𝑐=2
𝑦 = 𝑚𝑥 + 2
2
Our equation of the line is ∴ 𝑦 = − 5 𝑥 + 2
1
3. a) (1; 2) and (3; 6) b) (3; 2) and (-1; 6)
First, we find the gradient First, we find the gradient
𝑦 −𝑦 𝑦 −𝑦
𝑚 = 𝑥2−𝑥1 𝑚 = 𝑥2−𝑥1
2 1 2 1
1
6− 6−2
2
𝑚 = 3−1 𝑚 = −1−3
11 3
𝑚= 𝑜𝑟 2 4 𝑚 = −1
4
4. a) 𝑦 = 3𝑥 + 3 and 𝑦 = 3𝑥 + 6
Parallel – the gradients are the same (both are 3)
b) 𝑦 = 3𝑥 + 3 and 𝑦 = −3𝑥 + 6
3 × −3 = −9 not = -1
Neither parallel nor perpendicular
1
c) 𝑦 = 3𝑥 + 3 and 𝑦 = −3𝑥 + 6
1
3 × − 3 = −1
The lines are perpendicular.
d) 𝑦=3 and 𝑥=3
The lines are perpendicular because the first is aa horizontal line, and the
second is a vertical line, and they cross at a right angle to each other.
e) 𝑦=3 and 𝑦=5
These lines are parallel because they are both horizontal lines. (Their gradients
are both equal to 0)
9|Page
1
f) 𝑦 = −2𝑥 + 4 and 𝑦 = 𝑥+3
2
1
−2 × 2 = −1
These lines are perpendicular.
Activity 3
1. a)
b)
10 | P a g e
c)
d)
11 | P a g e
e)
2. a) 𝑦 = 𝑥2 + 1 and 𝑦 = 𝑥2 − 1
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: 1 < 𝑦 < ∞ Range: −1 < 𝑦 < ∞
b) 𝑦 = 2𝑥 2 + 1 and 𝑦 = −2𝑥 2 + 1
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: 1 < 𝑦 < ∞ Range: −∞ < 𝑦 < 1
1
c) 𝑦 = 3𝑥 2 + 2 and 𝑦 = 3 𝑥2 + 2
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: 2 < 𝑦 < ∞ Range: 2 < 𝑦 < ∞
d) 𝑦 = 4𝑥 2 − 5 and 𝑦 = 4𝑥 2 − 3
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: −5 < 𝑦 < ∞ Range: −3 < 𝑦 < ∞
12 | P a g e
1
e) 𝑦 = 𝑥2 + 1 and 𝑦 = −2𝑥 2 + 1
2
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: 1 < 𝑦 < ∞ Range: −∞ < 𝑦 < 1
3. a) 𝑦 = 𝑥2 + 1 and 𝑦 = 𝑥2 − 1
TP: (0; q) TP: (0; q)
∴ (0; 1) ∴ (0; -1)
Axis of symmetry: 𝑥 = 0 Axis of symmetry: 𝑥 = 0
b) 𝑦 = 2𝑥 2 + 1 and 𝑦 = −2𝑥 2 + 1
TP: (0; q) TP: (0; q)
∴ (0; 1) ∴ (0; 1)
Axis of symmetry: 𝑥 = 0 Axis of symmetry: 𝑥 = 0
1
c) 𝑦 = 3𝑥 2 + 2 and 𝑦 = 3 𝑥2 + 2
TP: (0; q) TP: (0; q)
∴ (0; 2) ∴ (0; 2)
Axis of symmetry: 𝑥 = 0 Axis of symmetry: 𝑥 = 0
d) 𝑦 = 4𝑥 2 − 5 and 𝑦 = 4𝑥 2 − 3
TP: (0; q) TP: (0; q)
∴ (0; -5) ∴ (0; -3)
Axis of symmetry: 𝑥 = 0 Axis of symmetry: 𝑥 = 0
1
e) 𝑦 = 2 𝑥2 + 1 and 𝑦 = −2𝑥 2 + 1
TP: (0; q) TP: (0; q)
∴ (0; 1) ∴ (0; 1)
Axis of symmetry: 𝑥 = 0 Axis of symmetry: 𝑥 = 0
13 | P a g e
4. a) The graph with a turning point (0; -4) and passing through the point
(4; 12).
The turning point is (0; q) therefore we can say: 𝑦 = 𝑎𝑥 2 − 4
Now we substitute in the second coordinate:
12 = 𝑎(4)2 − 4
16 = 16𝑎
∴𝑎=1
Our equation is ∴ 𝑦 = 𝑥 2 − 4
b) The graph with the y-intercept at 2 and passing through the point (3; -25)
The y-intercept is the turning point (0; q) = (0; 2), ∴ 𝑦 = 𝑎𝑥 2 + 2
Now we substitute in the coordinate (3; -25):
−25 = 𝑎(3)2 + 2
∴ −27 = 9𝑎
∴ 𝑎 = −3
Our equation is ∴ 𝑦 = −3𝑥 2 + 2
c) From the graph we have the point A = (-3; -6) and the turning point is
(0; 3), so we can say 𝑦 = 𝑎𝑥 2 + 3
Now we substitute in A:
−6 = 𝑎(−3)2 + 3
∴ −9 = 9𝑎
∴ 𝑎 = −1
Our equation is ∴ 𝑦 = −𝑥 2 + 3
d) The graph passing through the points A (-6; 10) and B (4; 0).
We can substitute A and B to get two equations:
10 = 𝑎(−6)2 + 𝑞 0 = 𝑎(4)2 + 𝑞
10 = 36𝑎 + 𝑞 0 = 16𝑎 + 𝑞
10 − 36𝑎 = 𝑞 …1 −16𝑎 = 𝑞 …2
Now we substitute equation 1 into equation 2 and solve for a:
10 − 36𝑎 = −16𝑎
10 = 20𝑎
1
∴𝑎=2
14 | P a g e
e) From the graph we have that A = (3; 4) and the turning point is (0; 1).
This means that we can write: 𝑦 = 𝑎𝑥 2 + 1
Now we substitute A in:
4 = 𝑎(3)2 + 1
3 = 9𝑎
1
𝑎=3
1
This means that our equation is given by: 𝑦 = 3 𝑥 2 + 1
f) The graph passing through the points A (-1; 1) and B (3; 17)
We can substitute A and B to get two equations:
1 = 𝑎(−1)2 + 𝑞 17 = 𝑎(3)2 + 𝑞
1=𝑎+𝑞 17 = 9𝑎 + 𝑞
1−𝑎 =𝑞 …1 17 − 9𝑎 = 𝑞 …2
Now we substitute equation 1 into equation 2 and solve for a:
1 − 𝑎 = 17 − 9𝑎
1 − 17 = −9𝑎 + 𝑎
−16 = −8𝑎
𝑎=2
g) The graph passing through the points A (-2; 16) and B (4; 52)
We can substitute A and B to get two equations:
16 = 𝑎(−2)2 + 𝑞 52 = 𝑎(4)2 + 𝑞
16 = 4𝑎 + 𝑞 52 = 16𝑎 + 𝑞
16 − 4𝑎 = 𝑞 …1 52 − 16𝑎 = 𝑞 …2
15 | P a g e
5. a) 𝑦 = 𝑥2 − 4
Domain: −∞ < 𝑥 < ∞ Range: −4 < 𝑦 < ∞
b) 𝑦 = −3𝑥 2 + 2
Domain: −∞ < 𝑥 < ∞ Range: −∞ < 𝑦 < 2
c) 𝑦 = −𝑥 2 + 3
Domain: −∞ < 𝑥 < ∞ Range: −∞ < 𝑦 < 3
1
d) 𝑦 = 2 𝑥2 − 8
Domain: −∞ < 𝑥 < ∞ Range: −8 < 𝑦 < ∞
1
e) 𝑦 = 3 𝑥2 + 1
Domain: −∞ < 𝑥 < ∞ Range: 1 < 𝑦 < ∞
f) 𝑦 = 2𝑥 2 − 1
Domain: −∞ < 𝑥 < ∞ Range: −1 < 𝑦 < ∞
g) 𝑦 = 3𝑥 2 + 4
Domain: −∞ < 𝑥 < ∞ Range: 4 < 𝑦 < ∞
6. a) 𝑦 = 𝑥2 − 4
TP: (0; -4) Axis of symmetry: 𝑥 = 0
b) 𝑦 = −3𝑥 2 + 2
TP: (0; 2) Axis of symmetry: 𝑥 = 0
16 | P a g e
c) 𝑦 = −𝑥 2 + 3
TP: (0; 3) Axis of symmetry: 𝑥 = 0
1
d) 𝑦 = 2 𝑥2 − 8
TP: (0; -8) Axis of symmetry: 𝑥 = 0
1
e) 𝑦 = 3 𝑥2 + 1
TP: (0; 1) Axis of symmetry: 𝑥 = 0
f) 𝑦 = 2𝑥 2 − 1
TP: (0; -1) Axis of symmetry: 𝑥 = 0
g) 𝑦 = 3𝑥 2 + 4
TP: (0; 4) Axis of symmetry: 𝑥 = 0
Activity 4
1. a)
17 | P a g e
b)
c)
18 | P a g e
d)
e)
2
2. a) 𝑦=𝑥 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < 0 𝑎𝑛𝑑 0 < 𝑦 < ∞
19 | P a g e
−2
𝑦= Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
𝑥
Range: −∞ < 𝑦 < 0 𝑎𝑛𝑑 0 < 𝑦 < ∞
3
b) 𝑦=𝑥 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < 0 𝑎𝑛𝑑 0 < 𝑦 < ∞
𝑥
𝑦=3 Domain: −∞ < 𝑥 < ∞
Range: −∞ < 𝑦 < ∞
4
c) 𝑦 =𝑥+1 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < 1 𝑎𝑛𝑑 1 < 𝑦 < ∞
4
𝑦 =𝑥−2 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < −2 𝑎𝑛𝑑 − 2 < 𝑦 < ∞
−3
d) 𝑦= +3 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
𝑥
Range: −∞ < 𝑦 < 3 𝑎𝑛𝑑 3 < 𝑦 < ∞
3
𝑦 =𝑥−3 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < −3 𝑎𝑛𝑑 − 3 < 𝑦 < ∞
5
e) 𝑦=𝑥 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < 0 𝑎𝑛𝑑 0 < 𝑦 < ∞
7
𝑦=𝑥 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < 0 𝑎𝑛𝑑 0 < 𝑦 < ∞
2 −2
3. a) 𝑦=𝑥 and 𝑦= 𝑥
Asym: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 0 Asym: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 0
Axes: 𝑦 = 𝑥 𝑎𝑛𝑑 𝑦 = −𝑥 Axes: 𝑦 = 𝑥 𝑎𝑛𝑑 𝑦 = −𝑥
3 𝑥
b) 𝑦=𝑥 and 𝑦=3
Asym: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 0 Asym: none
Axes: 𝑦 = 𝑥 𝑎𝑛𝑑 𝑦 = −𝑥 Axes: none
4 4
c) 𝑦 =𝑥+1 and 𝑦 =𝑥−2
Asym: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 1 Asym: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = −2
Axes: 𝑦 = 𝑥 + 1 𝑎𝑛𝑑 𝑦 = −𝑥 + 1 Axes: 𝑦 = 𝑥 − 2 𝑎𝑛𝑑 𝑦 = −𝑥 − 2
20 | P a g e
−3 3
d) 𝑦= +3 and 𝑦 = −3
𝑥 𝑥
Asym: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 3 Asym: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = −3
Axes: 𝑦 = 𝑥 + 3 𝑎𝑛𝑑 𝑦 = −𝑥 + 3 Axes: 𝑦 = 𝑥 − 3 𝑎𝑛𝑑 𝑦 = −𝑥 − 3
5 7
e) 𝑦=𝑥 and 𝑦=𝑥
Asym: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 0 Asym: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 0
Axes: 𝑦 = 𝑥 𝑎𝑛𝑑 𝑦 = −𝑥 Axes: 𝑦 = 𝑥 𝑎𝑛𝑑 𝑦 = −𝑥
*You can check that you have found the correct equation by typing it into
your table mode and looking for both of your points. If they are both there,
your equation is correct.
1
d) The graph passing through the 𝑥-intercept (2 2 ; 0) and with the asymptote
𝑦 = −2.
𝑎
This means that we can write our equation as: 𝑦 = 𝑥 − 2
Now we substitute in the point and solve for a:
𝑎
0= 1 −2
2
2
0=𝑎−5
∴𝑎=5
5
This means that our equation is ∴ 𝑦 = 𝑥 − 2
e) We are given the three points: (-1; 5), (-3; 3) and (3; 1).
We substitute in any two of the points and solve simultaneously (if you selected
different points than the one in this solution, don’t panic, just make sure that you
get the same equation at the end, and follow the same process).
We are going to substitute in (-1; 5) and (3; 1)
𝑎 𝑎
5 = −1 + 𝑞 1= 3+𝑞
5 = −𝑎 + 𝑞 3 = 𝑎 + 3𝑞
5+𝑎 =𝑞 …1 3 − 3𝑞 = 𝑎 …2
3 − 3(5 + 𝑎) = 𝑎
3 − 15 − 3𝑎 = 𝑎
−12 = 4𝑎
∴ 𝑎 = −3
Now we can solve for q:
𝑞 = 5 + (−3)
∴𝑞=2
−3
This means that our equation is ∴ 𝑦 = 𝑥 + 2
4
5. a) 𝑦 =𝑥−2 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < −2 𝑎𝑛𝑑 − 2 < 𝑦 < ∞
−3
b) 𝑦= +5 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
𝑥
Range: −∞ < 𝑦 < 5 𝑎𝑛𝑑 5 < 𝑦 < ∞
9
c) 𝑦 =𝑥+3 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < 3 𝑎𝑛𝑑 3 < 𝑦 < ∞
5
d) 𝑦 =𝑥−2 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
Range: −∞ < 𝑦 < −2 𝑎𝑛𝑑 − 2 < 𝑦 < ∞
−3
e) 𝑦= +2 Domain: −∞ < 𝑥 < 0 𝑎𝑛𝑑 0 < 𝑥 < ∞
𝑥
Range: −∞ < 𝑦 < 2 𝑎𝑛𝑑 2 < 𝑦 < ∞
4
6. a) 𝑦 =𝑥−2 Asymptotes: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = −2
Axes of Symmetry: 𝑦 =𝑥−2 𝑎𝑛𝑑 𝑦 = −𝑥 − 2
−3
b) 𝑦= +5 Asymptotes: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 5
𝑥
Axes of Symmetry: 𝑦 =𝑥+5 𝑎𝑛𝑑 𝑦 = −𝑥 + 5
9
c) 𝑦 =𝑥+3 Asymptotes: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 3
Axes of Symmetry: 𝑦 =𝑥+3 𝑎𝑛𝑑 𝑦 = −𝑥 + 3
5
d) 𝑦 =𝑥−2 Asymptotes: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = −2
Axes of Symmetry: 𝑦 =𝑥−2 𝑎𝑛𝑑 𝑦 = −𝑥 − 2
−3
e) 𝑦= +2 Asymptotes: 𝑥 = 0 𝑎𝑛𝑑 𝑦 = 2
𝑥
Axes of Symmetry: 𝑦 =𝑥+2 𝑎𝑛𝑑 𝑦 = −𝑥 + 2
23 | P a g e
Activity 5
1. a)
b)
24 | P a g e
c)
d)
25 | P a g e
e)
2. a) 𝑦 = 2𝑥 and 𝑦 = −2𝑥
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: 0 < 𝑦 < ∞ Range: −∞ < 𝑦 < 0
b) 𝑦 = 3𝑥 and 𝑦 = 2(3𝑥 )
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: 0 < 𝑦 < ∞ Range: 0 < 𝑦 < ∞
c) 𝑦 = 5𝑥 + 1 and 𝑦 = 5𝑥 − 2
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: 1 < 𝑦 < ∞ Range: −2 < 𝑦 < ∞
d) 𝑦 = −3𝑥 + 3 and 𝑦 = 3𝑥 − 3
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: −∞ < 𝑦 < 3 Range: −3 < 𝑦 < ∞
1 𝑥 1 𝑥
e) 𝑦 = (2) and 𝑦 = (3)
Domain: −∞ < 𝑥 < ∞ Domain: −∞ < 𝑥 < ∞
Range: 0 < 𝑦 < ∞ Range: 0 < 𝑦 < ∞
26 | P a g e
3. a) 𝑦 = 2𝑥 and 𝑦 = −2𝑥
Asymptote: 𝑦 = 0 Asymptote: 𝑦 = 0
b) 𝑦 = 3𝑥 and 𝑦 = 2(3𝑥 )
Asymptote: 𝑦 = 0 Asymptote: 𝑦 = 0
c) 𝑦 = 5𝑥 + 1 and 𝑦 = 5𝑥 − 2
Asymptote: 𝑦 = 1 Asymptote: 𝑦 = −2
d) 𝑦 = −3𝑥 + 3 and 𝑦 = 3𝑥 − 3
Asymptote: 𝑦 = 3 Asymptote: 𝑦 = −3
1 𝑥 1 𝑥
e) 𝑦=( ) and 𝑦=( )
2 3
Asymptote: 𝑦 = 0 Asymptote: 𝑦 = 0
1
b) The graph with the points (−1; 2 3) and (3; 29) when a = 1.
We don’t have the tools in grade 10 to solve this equation simultaneously. But we
can use logic and trial and error to solve it (which is why I have left this example
in here).
We know that our equation has the form: 𝑦 = 𝑏 𝑥 + 𝑞
27 | P a g e
So, I am going to put the points into a table, and then make educated guesses for
the values of b and q, based on what we know from our coordinates and the form
that our equation takes:
𝒙 𝒚 If b= Then q =
1
1 2 = 2−1 + 𝑞
-1 2 2 3
3 5
∴𝑞=1
6
3 29 2 29 = 23 + 𝑞
∴ 𝑞 = 21
Because the q values for the coordinates don’t match, we try again.
𝒙 𝒚 If b= Then q =
1 1 −1
1 1 2 =( ) +𝑞
-1 2 3 2
3 2 1
∴𝑞=
3
1 3
3 29 1 29 = (2) + 𝑞
2 7
∴ 𝑞 = 28 8
Because the q values for the coordinates don’t match, we try again.
𝒙 𝒚 If b= Then q =
1
-1 1 3 2 = 3−1 + 𝑞
2 3
3 ∴𝑞=2
3 29 3 29 = 33 + 𝑞
∴𝑞=2
Now the q values are the same for both coordinates which means that we have
found our b and q values.
Our equation is ∴ 𝑦 = 3𝑥 + 2
c) The coordinates given are (0; 2) and (1; 0.5), and the asymptote is 𝑦 = 0
Our equation therefore has the form 𝑦 = 𝑎. 𝑏 𝑥
28 | P a g e
1
d) The graph passing through the points (1; −1 4) and (-2; 46) and with the
asymptote 𝑦 = −2
From the information we can write: 𝑦 = 𝑎. 𝑏 𝑥 − 2
Now we substitute in the two points:
1
−1 4 = 𝑎. 𝑏1 − 2 46 = 𝑎. 𝑏 −2 − 2
3 𝑎
= 𝑎. 𝑏 …1 48 = 𝑏2
4
48𝑏 2 = 𝑎 …2
Now we substitute equation 2 into 1:
3
= (48𝑏 2 ). 𝑏
4
3
= 48𝑏 3
4
1
= 𝑏3
64
3 1
√ =𝑏
64
1
∴𝑏=4
1 𝑥
Our equation is ∴ 𝑦 = 3. (4) − 2
29 | P a g e
e) The exponential graph with the equation 𝑦 = 𝑏 𝑥 + 𝑞 and the points are given as
(0; 0), and (2; 3). The asymptote is y = -1.
From the information given we can first write that 𝑦 = 𝑏 𝑥 − 1
(0; 0) will not give us any further information because anything to the power of 0
is 1 and this will not help us to find b. So, we substitute for the other point (2; 3)
to find b.
3 = 𝑏2 − 1
4 = 𝑏2
∴ 𝑏 = 2.
This means that our equation is ∴ 𝑦 = 2𝑥 − 1
1 𝑥
5. a) 𝑦 = (2) + 2
Domain: −∞ < 𝑥 < ∞ Range: 2 < 𝑦 < ∞
b) 𝑦 = 3𝑥 + 2
Domain: −∞ < 𝑥 < ∞ Range: 2 < 𝑦 < ∞
1 𝑥
c) 𝑦 = 2. (4)
Domain: −∞ < 𝑥 < ∞ Range: 0 < 𝑦 < ∞
1 𝑥
d) 𝑦 = 3 (4) − 2
Domain: −∞ < 𝑥 < ∞ Range: −2 < 𝑦 < ∞
e) 𝑦 = 2𝑥 − 1
Domain: −∞ < 𝑥 < ∞ Range: −1 < 𝑦 < ∞
1 𝑥
6. a) 𝑦 = (2) + 2 Asymptote: 𝑦 = 2
b) 𝑦 = 3𝑥 + 2 Asymptote: 𝑦 = 2
1 𝑥
c) 𝑦 = 2. (4) Asymptote: 𝑦 = 0
1 𝑥
d) 𝑦 = 3 (4) − 2 Asymptote: 𝑦 = −2
e) 𝑦 = 2𝑥 − 1 Asymptote: 𝑦 = −1
30 | P a g e
Activity 6
1. a) When the straight-line graph is horizontal, the 𝑥-value is constant and the
gradient is undefined.
False, when the straight-line graph is horizontal, the y-value is constant
and the gradient is 0.
OR – when the straight-line graph is vertical, the 𝑥-value is constant and the
gradient is undefined.
𝑘
b) The equation for the hyperbola is given by 𝑦 = 𝑥 + 𝑝
True – note here: the letters (variables) used (in this case k and p), do not
affect the equation in any way, it is only their position that matters.
c) When a > 0 the graph of an exponential graph is a sad face.
False – when a > 0 the graph of an exponential graph is happy, that is, it points
upwards.
d) The parabola has two 𝑥-intercepts, while all the other graphs only have one.
True, only when q < 0 and a > 0, or when q > 0 and a < 0.
e) The exponential graph can have values for b < 0.
False, the exponential graph cannot ever have values for b < 0.
0 = 𝑎(−2)2 − 8
8 = 4𝑎
∴𝑎=2
Our equation is ∴ 𝑦 = 2𝑥 2 − 8
b) The graphs will not intersect again – they only cross each other once, as
each graph is a one-to-one function and the exponential graph cannot pass
through the asymptote.
b) We solve simultaneously:
𝑦 = −3𝑥 2 + 12 …1 𝑦 = 2𝑥 + 4 …2
Substitute 2 into 1:
2𝑥 + 4 = −3𝑥 2 + 12
0 = −3𝑥 2 − 2𝑥 + 12 − 4
0 = −3𝑥 2 − 2𝑥 + 8
0 = 3𝑥 2 + 2𝑥 − 8
0 = (𝑥 + 2)(3𝑥 − 4)
4
∴ 𝑥 = −2 𝑎𝑛𝑑 𝑥 = 3
This is D Substitute back into 2:
4
𝑦 = 2 (3) + 4
2
𝑦 = 63
1 2
∴ the coordinate for H is (1 3 ; 6 3)
c) No, we do not have the tools to solve the intersection of an exponential graph with
a quadratic equation.
0 = −3(𝑥 2 − 4)
0 = −3(𝑥 + 2)(𝑥 − 2)
∴ 𝑥 = −2 𝑎𝑛𝑑 𝑥 = 2
This is D And this is E (2; 0)
e) 𝑥=0
f) If the graph is shifted down by 3 units, the new equation becomes: 𝑦 = −3𝑥 2 + 9
Now we let y = 0 and solve for 𝑥:
0 = −3𝑥 2 + 9
0 = −3(𝑥 2 − 3)
0 = −3(𝑥 + √3)(𝑥 − √3)
∴ 𝑥 = −√3 𝑎𝑛𝑑 𝑥 = √3
So, our new 𝑥-intercepts are (−√3 ; 0) 𝑎𝑛𝑑 (√3 ; 0)